2006
DOI: 10.1124/jpet.106.105247
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Plant Cannabinoids with Emphasis on the Effect of Cannabidiol on Human Breast Carcinoma

Abstract: ⌬9 -Tetrahydrocannabinol (THC) exhibits antitumor effects on various cancer cell types, but its use in chemotherapy is limited by its psychotropic activity. We investigated the antitumor activities of other plant cannabinoids, i.e., cannabidiol, cannabigerol, cannabichromene, cannabidiol acid and THC acid, and assessed whether there is any advantage in using Cannabis extracts (enriched in either cannabidiol or THC) over pure cannabinoids. Results obtained in a panel of tumor cell lines clearly indicate that, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
467
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(492 citation statements)
references
References 37 publications
18
467
4
3
Order By: Relevance
“…The same group used the same approach to assess CBD effects at human TRPV1 expressed in HEK293 cells for a third and final time [71]. Again, some disparity between the results presented and those previously published was evident as CBD's efficacy was consistent with that reported by Ligresti et al [99] but not that reported by Bisogno et al [19]; however, potency differed from both preceding papers (EC 50: 1.0 μM vs 6.3μM ( [71] estimated from Ligresti et al [99] vs 3.5 μM [19]). Taken together, these results suggest that CBD can submaximally activate TRPV1 receptors, although the potency of CBD's effects remains less well defined.…”
Section: Trp Channelsmentioning
confidence: 51%
See 2 more Smart Citations
“…The same group used the same approach to assess CBD effects at human TRPV1 expressed in HEK293 cells for a third and final time [71]. Again, some disparity between the results presented and those previously published was evident as CBD's efficacy was consistent with that reported by Ligresti et al [99] but not that reported by Bisogno et al [19]; however, potency differed from both preceding papers (EC 50: 1.0 μM vs 6.3μM ( [71] estimated from Ligresti et al [99] vs 3.5 μM [19]). Taken together, these results suggest that CBD can submaximally activate TRPV1 receptors, although the potency of CBD's effects remains less well defined.…”
Section: Trp Channelsmentioning
confidence: 51%
“…Notably, other molecular targets of CBD are present in HEK293 cells (e.g., VDAC1; see Tables 1, 2, 3 and 4) but their expression on intracellular membranes is likely to prevent CBD-mediated effects from being identified by an assay such as this. This group used the same approach in a later study that examined anticancer effects of CBD [99], where CBD effects at human TRPV1 expressed in HEK293 cells were again assessed and reported in the same way as above. While specific EC 50 and efficacy results for were not formally presented, an estimate from the concentration-response curves published in suggests that CBD was both less efficacious (~50% vs 70%) and less potent (~6.3 μM vs 3.5 μM) than previously reported [99].…”
Section: Trp Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, two different tumor cell lines transplanted to hairless mice were half as big as those of the untreated group, and both breast-and lung-cancer cells injected to paws showed approximately three times less metastatic invasion. 112 An inhibitor of basic helix-loop-helix transcription factors (Id1) has recently been shown to be a key regulator of the metastatic potential of breast and additional cancers. CBD could down-regulate the Id-1 expression in aggressive human breast cancer cells, and the concentrations effective at inhibiting Id-1 expression correlated with those used to inhibit the proliferative and invasive phenotype of breast cancer cells.…”
Section: Anticancer Actionmentioning
confidence: 99%
“…CBD does not have appreciable affinity for CB 1 or CB 2 receptors and does not have psychotropic activities (10). CBD has been shown to inhibit breast cancer metastasis in vivo in mice (11). However, modulation of a distinct signaling pathway that would explain the inhibitory action of CBD on breast cancer metastasis has not been elucidated.…”
mentioning
confidence: 99%